Analysis of congenital heart surgery results: A comparison of four risk scoring systems - Yıldız, Okan; Kasar, Taner; Ozturk, Erkut; Tüzün, Behzat; Altın, Hüsnü Fırat; Onan, Ismihan Selen; Haydin, Sertac (My University, 2018)
Background: This study aims to evaluate the surgical results of our clinic according to presumption systems of Risk Adjustment in Congenital Heart Surgery, Aristotle Basic Complexity score, Aristotle Comprehensive Complexity score, and Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality categories and to compare the efficiency of these systems in predicting morbidity and mortality.Methods: In the study, classification and the risk scoring were performed with the four different systems for 1,950 patients (1,038 males, 912 females; mean age 5.5 months; range, 1 day to 18 years) who were administered congenital heart surgery between 1 October 2012 and 31 December 2016. The hospital mortality and morbidity were calculated for each category from the four models. The discriminatory ability of the models was determined by calculating the area under the receiver operating characteristic curve and the receiver operating characteristic curves of the four models were compared.Results: Median weight of the patients was 7.2 kg (range, 1.8-80 kg). Among the patients, 53% were males and 47.5% were younger than one year of age. Of totally 1,950 operations, mortality was observed in 149 (7.6%) and morbidity was observed in 541 (27.7%). Areas under the receiver operating characteristic curve for mortality were 0.803, 0.795, 0.729, and 0.712 for the Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality categories, Aristotle Comprehensive Complexity, Risk Adjustment in Congenital Heart Surgery, and Aristotle Basic Complexity scores, respectively. Areas under the receiver operating characteristic curve for morbidity were 0.732, 0.731, 0.730, and 0.685 for the Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality categories, Risk Adjustment in Congenital Heart Surgery, Aristotle Comprehensive Complexity, and Aristotle Basic Complexity scores, respectively.Conclusion: Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality categories, Risk Adjustment in Congenital Heart Surgery, Aristotle Basic Complexity, and Aristotle Comprehensive Complexity score systems were effective in predicting the morbidities and mortalities of patients who underwent congenital heart surgery and evaluating the performance of the surgical centers. Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery mortality categories were on the forefront due to high feasibility and performance. Aristotle Basic Complexity score system had the lowest performance. Combinations of systems will provide the most benefit during evaluation of results.
Keywords: Tıbbi Araştırmalar Deneysel; Kalp ve Kalp Damar Sistemi; Cerrahi